High PGAM5 expression induces chemoresistance by enhancing Bcl-xL-mediated anti-apoptotic signaling and predicts poor prognosis in hepatocellular carcinoma patients. Issue 10 (October 2018) - Cheng, Jingjing; Qian, Dong; Ding, Xiaofeng; Song, Tianqiang; Cai, Muyan; Xie,; Wang, Yuwen; Zhao, Jinlin; Liu, Zhuang; Wu, Zhiqiang; Pang, Qingsong; Zhu, Li; et al.
Abstract Hepatocellular carcinoma (HCC) is the one of most common and deadly cancers, and is also highly resistant to conventional chemotherapy treatments. Mitochondrial phosphoglycerate mutase/protein phosphatase (PGAM5) regulates mitochondrial homeostasis and cell death, however, little is known about its roles in cancer. The aim of this study was to explore the clinical significance and potential biological functions of PGAM5 in hepatocellular carcinoma. For the first time, our results show that PGAM5 is significantly upregulated in HCC compared with corresponding adjacent noncancerous hepatic tissues and high PGAM5 expression is an independent predictor of reduced survival times in both univariate and multivariate analyses. Additionally, in vivo and in vitro studies showed that depleting PGAM5 expression inhibited tumor growth and increased the 5-fluorouracil sensitivity of HCC cells. Conversely, restoring PGAM5 expression in PGAM5-knockdown cells dramatically enhanced HCC cell resistance to 5-fluorouracil. Importantly, we demonstrated that the mechanism of 5-fluorouracil resistance conferred to HCC cells by PGAM5 was via inhibiting BAX- and cytochrome C-mediated apoptotic signaling by interacting and stabilizing Bcl-xL. Consistently, in the same cohorts of HCC patient tissues, Bcl-xL expression was positively correlated with PGAM5, and together predicted poor prognoses. In Conclusion, Our data highlight the molecular etiology and clinical significance of PGAM5 in HCC. Targeting the novel signaling pathway mediated by PGAM5/Bcl-xL may represent a new therapeutic strategy to improve the survival outcomes of HCC patients.